Models of strategic planning in the family business - Araya Leandro, Arnoldo (2017)
This research presents a literature review on models of strategic planning in family businesses. Strategic planning in family business is a decision-making diagnostic process, methodical, introspective and collective, about the current activities of the family business, and the path it should take in the future to adjust to the changes and demands of the environment and the family structure, in order to keep the continuity over time with successful business results. Every family company that wants the family to remain as owner of the company from generation to generation, should plan what they will do to make it possible. This plan cannot ignore the strategic business plan and the strategic family plan, so that both jointly achieve the goals proposed.